Pengaruh Budaya Organisasi, Motivasi Dan Komitmen Organisasi Terhadap Kinerja Organisasi (Studi Kasus Himpunan Mahasiswa Program Studi Manajemen, Akuntansi Dan Perbankan Syariah Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Jefri Purnama; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aims to determine the effect of organizational culture, motivation and organizational commitment on organizational performance. The data used in this study uses primary data by distributing questionnaires to respondents. The research population is the management of the Student Activity Unit of the Faculty of Economics and Business (UAM), while the sample used is the Student Association of the Management, Accounting and Banking Studies Program at the Faculty of Economics and Business, Islamic University of Malang. The research sample was taken from the population using a sampling technique in the form of purposive sampling method. The results obtained by using multiple linear regression test Y = 18.977 + 0.758X1 + 0.845X2 + 0.439X3 + e, and the test of this study used the f test and t test. The results of this study indicate that partially organizational culture influences organizational performance, motivation influences organizational performance, and commitment influences organizational commitment. While simultaneously organizational culture, motivation and organizational commitment affect organizational performance.Keywords: Organizational Culture, Motivation, Organizational Commitment and Organizational Performance